Characteristics of Ore Pass-Related Seismicity at Kiirunavaara Mine, Kiruna, Sweden - Parente da Silva Alem Marinho, Gabriel (Luleå tekniska universitet, Geoteknologi, 2024)
The Kiirunavaara Mine in the north of Sweden turned seismically active with large damaging events in 2007. Therefore, a mine-wide seismic system was installed in 2008 and has been continuously expanding since then. A large portion of the recorded seismic events with ML ≥ -1.5 in the footwall (61%) is related to the ore passes. Even though the majority of these events are ore pass “noise” (events originated by impacts of falling ore on the ore pass walls), the ore pass-related events (OPE) represent a problem to the estimation of the seismic hazard in the mine. The largest recorded event (Mw 4.2) could be classified as OPE. For that reason, it is necessary to systematically investigate the ore pass-related seismicity (OPS), and how this phenomenon evolved in space and time. The ore pass layout in the mine is unique as the 3-m wide ore passes are organized in groups of four, relatively close to each other, which is not a commonly used design. This proximity results in highly stressed pillars between them, which contributes to a fast deterioration of the ore pass walls. This process leads to an increased stress redistribution and seismicity in the pillars resulting in many large seismic events. The spatial distribution of the source parameters, as energy index, apparent stress, cumulative moment, cumulative energy, cumulative displacement, cumulative apparent volume of the OPE with ML ≥ -1.5 within a zone of 30 metres from the centre of the ore passes was analysed. The focal mechanism types and direction of the pressure axes were used to separate ore pass noise (-1.5 ≤ ML ≤ -0.5) from the genuine seismic events (ML > -0.5). The mechanism of the smaller OPE was tensile-type, with subvertical orientation of the pressure axes, whereas the larger OPE was compressive failure, with almost horizontal pressure axes. Large OPE (ML ≥ 1.5) were registered only around the studied southern ore pass groups (OP groups 26, OP 30, and OP 34), however their occurrence starts from OP 22 (not studied). The correlation between the ...